(untitled) (Research, Society and Development, 2020)
This study aimed to seek scientific evidence on syphilis in pregnant women and congenital syphilis that addressed epidemiology, prevention and control strategies in Brazil and worldwide, from an integrative literature review conducted at the following locations: Virtual Health Library, Library Online Scientific Electronics and Database: Latin American and Caribbean Health Sciences Literature and the US National Library of Medicine, 2009-2008. The sample consisted of 14 articles. The effects of mother-to-child transmission of syphilis are often devastating if the infection is not detected and treated in a timely manner in pregnancy. The results indicate that the incidence of syphilis in pregnant women and congenital are closely proportional to the unfavorable socioeconomic structure of countries, such as poverty, unemployment, little or no education, low prenatal coverage, is incident in underdeveloped countries and developed in the behavioral profile of women. unsafe sexual practices, promiscuity, alcohol and drug abuse. The prevention and control strategies were: improve syphilis screening; invest in health professionals and expand prenatal coverage.